THE EFFECT OF SERVICE QUALITY AND PRICE ON CUSTOMER SATISFACTION AND ITS IMPACT ON THE LOYALTY OF SIANTAR EXPRESS TRAIN CUSTOMERS - Khadijah Nurani; Rika Widianita; Ariyun Anisah (Jurnal Ilmiah MEA (Manajemen, Ekonomi, & Akuntansi), 2022)
The Siantar Express train is one of the transportations used by the people of Medan city to travel to Pematang Siantar and vice versa. The objective of this study is to test and analyze the effect of service quality, price on customer satisfaction and its impact on customer loyalty.The sampling technique used is Accidental Sampling which is sampling based on who are the members of the population who coincidentally meet the researcher who can provide the necessary information. The data analysis method is carried out by data analysis Path Analysis.Service quality has a positive and significant effect on customer satisfaction, price has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on customer loyalty, price has a positive and significant effect on customer loyalty, customer satisfaction has a positive and significant effect on customer loyalty, service quality has a positive and significant effect on customer loyalty through satisfaction customers, prices have a positive and significant effect on customer loyalty through customer satisfaction of the Siantar Express train. Siantar Express train customers will be loyal when using the Siantar Express train service, this is because the customer agrees to reuse the train service and suggests to others.